From authenticity assessments to new diplomacy - Tanodi, Branka (Centro de Investigaciones de la Facultad de Filosofía y Humanidades, 2007)
There is still scarce knowledge towards the fact of diplomatic as a science. The point of view at the beginning of XXI century is quite different to that of XVIII th. century. According to this outline, we intend to give a global vision of traditional doctine on diplomacy and actual points of view.